2015
DOI: 10.1148/radiol.14140568
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Receptor Type 2–targeted Contrast-enhanced US of Pancreatic Cancer Neovasculature in a Genetically Engineered Mouse Model: Potential for Earlier Detection

Abstract: Purpose To test ultrasonographic (US) imaging with vascular endothelial growth factor receptor type 2 (VEGFR2)-targeted microbubble contrast material for the detection of pancreatic ductal adenocarcinoma (PDAC) in a transgenic mouse model of pancreatic cancer development. Materials and Methods Experiments involving animals were approved by the Institutional Administrative Panel on Laboratory Animal Care at Stanford University. Transgenic mice (n = 44; Pdx1-Cre, KRasG12D, Ink4a−/−) that spontaneously develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 45 publications
(41 reference statements)
2
50
0
Order By: Relevance
“…General limitations of ultrasound as a screening tool, such as long imaging times and operator dependency, are already being addressed by the introduction of commercially available automated whole-breast ultrasound imaging systems that allow a time- and cost-efficient as well as more standardized acquisition and interpretation of breast ultrasound exams (30). In recent years, molecularly targeted ultrasound contrast agents have been developed to improve diagnostic accuracy of ultrasound in earlier detection of cancer such as pancreatic (15, 31), ovarian (32), and breast cancer (16, 19). To allow differentiation of cancer from non-cancerous tissue using ultrasound and molecularly-targeted contrast microbubbles, imaging targets have to be differentially expressed on the neovasculature of cancer compared to vessels in non-cancerous tissue.…”
Section: Discussionmentioning
confidence: 99%
“…General limitations of ultrasound as a screening tool, such as long imaging times and operator dependency, are already being addressed by the introduction of commercially available automated whole-breast ultrasound imaging systems that allow a time- and cost-efficient as well as more standardized acquisition and interpretation of breast ultrasound exams (30). In recent years, molecularly targeted ultrasound contrast agents have been developed to improve diagnostic accuracy of ultrasound in earlier detection of cancer such as pancreatic (15, 31), ovarian (32), and breast cancer (16, 19). To allow differentiation of cancer from non-cancerous tissue using ultrasound and molecularly-targeted contrast microbubbles, imaging targets have to be differentially expressed on the neovasculature of cancer compared to vessels in non-cancerous tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Pysz et al . showed that VEGFR2-targeted ultrasound imaging with BR55 can visualize down to sub-millimeter sized foci of pancreatic cancer in a transgenic mouse model (Pdx1-Cre, KRas G12D , Ink4a −/− ) and the in vivo targeted ultrasound imaging signal was ~30 fold higher in tumors compared to control normal pancreatic tissue, indicating that ultrasonic molecular imaging could be used for earlier pancreatic cancer detection in a screening setting of high risk patients [33]. Besides differentiating normal from cancer tissue, ultrasound molecular imaging using BR55 has been shown to assess breast cancer progression in a transgenic mouse model of breast cancer (FVB/N-Tg(MMTV-PyMT)634Mul) [32].…”
Section: Introductionmentioning
confidence: 99%
“…This significantly narrows down the diagnostic and therapeutic options of molecular US. 9,10 Moreover, the very short circulation time of MBs (half-life of 3-15 min) prevents effective targeting imaging and MB destruction for tumor-specific drug release. All these disadvantages seriously hamper the application of MB-based US molecular imaging and therapy.…”
Section: Introductionmentioning
confidence: 99%